2020
DOI: 10.1111/jfbc.13245
|View full text |Cite
|
Sign up to set email alerts
|

The immune‐enhancing potential of peptide fractions from fermented Spirulina platensis by mixed probiotics

Abstract: Mixed fermentation with different microorganisms can facilitate fermentation metabolism and increase the low molecular metabolites accumulation, thereby enhancing the bioactive activity. In this study, we evaluated the immune‐stimulating activities of Spirulina platensis and different extracts from fermented S. platensis (FS) by mixed probiotics in vitro, by measuring the proliferation and Th1/Th2 immunomodulatory potential on murine primary splenic lymphocytes. The results showed that mixed fermentation enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…An interesting observation was made by An et al. (2020), where the peptide fraction (<3 kDa) of Spirulina platensis, fermented by mixed probiotics, exhibited greater immune‐enhancing potential than the unfermented control. The peptide promoted lymphocyte proliferation and modulated the production of cytokines (IL‐2 and IL‐10).…”
Section: Immunity Boosting Nutraceuticalsmentioning
confidence: 93%
“…An interesting observation was made by An et al. (2020), where the peptide fraction (<3 kDa) of Spirulina platensis, fermented by mixed probiotics, exhibited greater immune‐enhancing potential than the unfermented control. The peptide promoted lymphocyte proliferation and modulated the production of cytokines (IL‐2 and IL‐10).…”
Section: Immunity Boosting Nutraceuticalsmentioning
confidence: 93%
“…Specific bacterial genera are involved in the production of GABA [ 49 ]. It was reported that LAB may induce the structural breakdown of cyanobacterial cell walls via hydrolysis, leading to the conversion of complex compounds [ 50 ]. Most of the glutamic acid and GABA-producing microorganisms are LAB, including species from the genera Lactococcus , Lactobacillus , Enterococcus and Streptococcus [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study highlights that fermented S. japonica exhibits higher phenolic and flavonoid contents compared with non‐fermented (Suraiya et al ., 2019). Various peptide fractions from Spirulina platensis, fermented by mix of microorganisms, significantly contribute to enhancing the immunomodulatory activities (An et al ., 2020). Fermented spirulina enhances the proliferation of lymphocytes compared to non‐fermented spirulina (An et al ., 2020).…”
Section: Health Benefits Associated With Fermented Algaementioning
confidence: 99%